THE SIGNIFICANCE OF RADIOIMMUNOIMAGING IN THE MANAGEMENT OF CANCER PATIENTS - Lin, Baohe; Yang, Zhi; Zhang, Qing; Xu, Xiaobao; Mu, Aping; Dong, Zhiwei; Zhang, Meiying (Chinese Journal of Cancer Research, 2013)
In this article, the significance of radioinmnmoimaging (RII) as a momitoring means for gastric colorectul and hmg cancer patients was reported. By using I- 131 or Tc- 99m labeled C50 (antiCF_A) and 3ml ( anti hmnan gastric cancer), 86 positive lesions were identified in 50 cancer patiens. 77 out of the 86 lesions (89.5%) were true positive, 4 false positive by post- surgecal pathology, biopsy or CY scan. The other 5 remained to be tmexplained and needed further follow-up. In our diulcal practice, RII with antitmnor McAbs suggested its anique value in the management of cancer patients. Totally, 14 occult lesions in 9 cancer patients missed by the other examination were identified by this technique. And owing to the RII findings, all of these patients got proper treatment in time.